L’université algérienne passe au mode e-Learning - BELLILET, Ouided (Journal of Human Sciences, 2022)
Even if education in general and university education in particular appears to be in a deontological duality between the in class courses and the distance-learning ones, both of them are able to coexist with a priority afforded to the pedagogic content in the face-to-face course in a real environment. But with the Covid-19 pandemic, digital technology has given e-Learning a step ahead and has given it an innovative dimension but not a unique one, since correspondence education has been recognized as a possibility for pupils who leaved the education system or were in an academic failure the possibility of continuing their studies.